Does the male gender govern conversion of laparoscopic cholecystectomy? - Manandhar, Kishor; Manandhar, Sujita (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Laparoscopic cholecystectomy (LC) occasionally demands conversion to open cholecystectomy (OC) because of multiple risk factors. This study was conducted to find out whether male gender is a stand-alone risk factors for conversion of LC to OC. Methods: This was a comparative analysis of conversion of LC to OC in patients operated for symptomatic cholelithiasis during June 2017 to May 2018 at Bir hospital, National Academy of Medical Sciences, Kathmandu, Nepal. The patients were divided into two groups: male (group 1) and female (group 2). Study variables included gender, America Society of Anesthesiologist class, history of upper abdominal pain within six weeks prior to surgery, upper abdominal surgery, emergency department visit due to upper abdominal pain, adhesion of gallbladder to adjacent structure and body mass index. Binominal logistic regression analysis of risk factors for conversion was conducted. Odds ratio (95% CI) was calculated. The p value ≤ 0.05 was considered statistically significant. Results: Among 151 patients (male 39, female 112), 7 (4.6%, male 3 and female 4) had conversion from LC to OC. Male gender itself as an isolated risk factor had no significant association to conversion (p=0.303). There was no significant difference found for age, operating time and hospital stay. Previous emergency visit (p=0.020) and adhesion (p<0.030) were associated with conversion. Conclusions: Male gender had no significant association for conversion of LC to open. Previous emergency visit due to upper abdominal pain and adhesion of gallbladder were associated risk factors for conversion.